The School Climate and Academic Mindset Inventory (SCAMI): Confirmatory Factor Analysis and Invariance Across Demographic Groups - Kearney, Christopher A.; Sanmartín, Ricardo; Gonzálvez, Carolina (Frontiers in Psychology, 2020)
School climate is a multidimensional construct of the quality of a student’s academic environment, often subsuming dimensions such as safety, instructional practices, social relationships, school facilities, and school connectedness. Positive school climate has beneficial effects on a wide range of adjustment variables in youth, including academic achievement, mental health, school attendance and graduation, and school-based behavior. Studies regarding school climate assessment have burgeoned in recent years but remain marked by limited sample sizes, narrow developmental levels, restricted items, unclear psychometric strength across multiple demographic groups, and lack of integration with key student education contextual factors such as academic mindset and social emotional learning. The present study evaluated a comprehensive measure of aspects of school climate, academic mindset, and social emotional learning in a sample of 105,379 diverse students (Mage = 13.47 years; SD = 2.47). The 9-factor structure of the School Climate and Academic Mindset Inventory was supported via confirmatory factor analysis. A trimmed model displayed adequate goodness-of-fit for males and females, younger age groups, and European American, biracial/multiracial, Hispanic, Native American, and Native Hawaiian/Pacific Islander students. The trimmed model was slightly less strong for older age groups as well as for African American and Asian American students. The scale may be useful for assessing school climate interventions, longitudinal climate patterns, and school-based algorithms of future performance, though additional validation of the scale remains necessary.